WORK-BASED LEARNING IN MIDWIFERY COMMUNITY PRACTICE AND ITS IMPACT ON STUDENT COMPETENCE - Hastuti Marlina; Sherly Vermita Warlenda (Journal of Public Health Science, 2026)
Midwifery education requires curriculum transformation, as approximately 35% to 42% of new graduates face adaptation challenges in primary care. Community practice often faces barriers to achieving initial competency targets, amounting to 20% to 30%. This study aims to analyze the effect of implementing Work-Based Learning (WBL) in midwifery community practice on improving student competency, encompassing knowledge, attitudes, and skills. The study used a quasi-experimental design with a one-group pretest-posttest design. The study population was all 43 students of the Undergraduate Midwifery Study Program at Hang Tuah University, Pekanbaru, in the regular academic year of 2025/2026. The sampling technique used was total sampling. Bivariate data analysis used a Paired Sample T-Test. The results showed a significance value of p = 0.000 (p < 0.05) for all aspects, confirming a significant effect of WBL implementation on improving student competency. The average score for knowledge increased from 68.42 to 86.75 with mean difference is 18.33, for attitudes from 71.15 to 89.20 with mean difference is 18.05, and for skills from 64.80 to 85.10 with mean difference is 20.30. It can be concluded that the WBL model has proven effective in bridging theory and field practice and enhancing students' clinical independence and cultural sensitivity. Recommendations for future research include using a control group and measuring the long-term retention of graduate competencies in the workplace.